Therapeutic actions of translocator protein (18 kDa) ligands in experimental models of psychiatric disorders and neurodegenerative diseases. Issue 154 (November 2015) - Arbo, B.D.; Benetti, F.; Garcia-Segura, L.M.; Ribeiro, M.F.
Highlights: TSPO ligands exert anxiolytic effects in rodents and humans. TSPO ligands exert neuroprotective actions in rodents. TSPO ligands promote peripheral axon regeneration. TSPO ligands induce changes in brain levels of neuroactive steroids. TSPO ligands decrease gliosis and neuroinflammation. Abstract: Translocator protein (TSPO) is an 18 kDa protein located at contact sites between the outer and the inner mitochondrial membrane. Numerous studies have associated TSPO with the translocation of cholesterol across the aqueous mitochondrial intermembrane space and the regulation of steroidogenesis, as well as with the control of some other mitochondrial functions, such as mitochondrial respiration, mitochondrial permeability transition pore opening, apoptosis and cell proliferation. In the brain, changes in TSPO expression occur in several neuropathological conditions including neurodegenerative diseases and psychiatric disorders. Furthermore, TSPO ligands have been shown to promote neuroprotection in animal models of brain pathology. At least in some cases, the mechanisms of neuroprotection are associated with modifications in brain steroidogenesis. In addition, regulation of neuroinflammation seems to be a common mechanism in the neuroprotective actions of TSPO ligands in different animal models of brain pathology.